Analisis Penggunaan Variasi Bahasa Arab Fusha Dan ‘Amiyah dalam Ruang Lingkup Sosial Bahasa (Sosiolinguistik) - Ni'mah, Rahma Azizatun (Institut Agama Islam Negeri Metro, 2024)
This study aims to analyze the variations of Arabic fusha and 'amiyah used in the social scope of language (sociolinguistics). The type of research used is descriptive qualitative research with library research method. The data analysis technique used in this study is content analysis technique including data reduction, data display, data verification and conclusion stages. The results of this study indicate that the difference between Arabic fusha and 'amiyah lies in the use of language rules. Therefore, the use of Arabic fusha and 'amiyah in social contexts is also different. Arabic fusha is used in formal forums, with a high social scope, while 'amiyah is often used in daily activities and communication that are non-formal, with a lower middle social scope. To study the differences in the use of Arabic fusha and 'amiyah in the social scope of the language, we must look at it from the aspect of word changes, pronunciation of letters in Arabic vocabulary and from the phonological aspect which includes: sound replacement, sound addition and sound deletion. This aims to find out the use of Arabic that is appropriate to the social context and to avoid misunderstandings in communicating with interlocutors who have various social backgrounds.